(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the collaborative efforts between nurses and physiotherapists in optimizing patient outcomes following orthopedic surgery. Highlighting the importance of comprehensive preoperative assessments, perioperative care, and postoperative rehabilitation, the collaboration aims to enhance patient recovery, reduce complications, and promote long-term musculoskeletal health.